An assessment of gender norms among students towards equality in higher education - Alam, M. Sultana; Suhaili, Samsudin; Mohamad Diah, Nurazzura (International Association of Multidisciplinary Research, 2015)
Measuring gender norms of young people are one of the important issues that have been attracted by the attention of the researchers in education. Currently, gender related violence, including sexual, physical, or psychological harm to girls and boys on the basis of their sex is common in the classroom as well as public domain. The purpose of this paper is to assess gender norms among students towards equality in higher education in Malaysia. The study was conducted in two higher learning institutions: International Islamic University Malaysia (IIUM) and Universiti Pendidikan Sultan Idris (UPSI) in Malaysia. A total of 300 students (77 males & 223 females) were selected as the respondents from the study areas using purposive sampling method. A survey research design was employed in this study. Questionnaires were completed in a supervised setting by the research protocol. The first objective of this study was to assess student’s attitudes towards equality at higher learning institutions from traditional and non-traditional perspectives. Results revealed that despite the majority of the respondents performed favourable attitudes towards equality; less favourable attitude towards gender equality was noted with respect to religious leadership and boys’ priority over girls in education. The study examined whether there is any difference between male and female student’s attitudes towards equality. Results showed that female students tended to have more egalitarian or non-traditional attitudes towards equality. The paper analyzed the relationship between the demographic characteristics and student’s attitudes towards equality. The results revealed that the ethnicity (r=0.26; p<0.01), region of residence (r=0.12; p<0.05), father’s educational level (r=0.117; p<0.043) and family members of studying were significantly related to the student’s attitudes towards equality.